2020
DOI: 10.1007/s12055-020-01060-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of CentriMag™ extracorporeal mechanical circulatory support use in critical cardiogenic shock (INTERMACS 1) patients

Abstract: Purpose Prognosis of patients presenting with INTERMACS 1 critical cardiogenic shock is generally poor. The aim of our study was to investigate the results of CentriMag™ extracorporeal short-term mechanical circulatory support as a bridge to decision in patients presenting with critical cardiogenic shock in our unit. Methods We retrospectively analysed 63 consecutive patients from January 2005 to June 2017, who were treated with a CentriMag™ device at our institution as a bridge to decision. Patients requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…In this patient cohort, almost half (46%) of the patients experienced major bleeding post‐operatively. This is similar to other single‐center studies that have reported high rates of bleeding events following STCF‐VAD implantation 1–3,7,10,32 . In two studies of patients supported with CentriMag devices, 38–75% of patients experienced at least one major bleeding event with almost one‐fifth requiring re‐operation 2,32 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this patient cohort, almost half (46%) of the patients experienced major bleeding post‐operatively. This is similar to other single‐center studies that have reported high rates of bleeding events following STCF‐VAD implantation 1–3,7,10,32 . In two studies of patients supported with CentriMag devices, 38–75% of patients experienced at least one major bleeding event with almost one‐fifth requiring re‐operation 2,32 .…”
Section: Discussionsupporting
confidence: 85%
“…This is similar to other single-center studies that have reported high rates of bleeding events following STCF-VAD implantation. [1][2][3]7,10,32 In two studies of patients supported with CentriMag devices, 38-75% of patients experienced at least one major bleeding event with almost one-fifth requiring re-operation. 2,32 In the current study, pre-implant MELD-XI scores were significantly associated with postoperative bleeding with those patients experiencing a bleed having a median MELD-XI score of 22.2 (IQR 17.1, 30.0).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During biventricular support, major bleedings may affect 20–40% of patients [ 27 , 28 ] and our preliminary findings showed a 17% rate of bleedings (non-fatal bronchial hemorrhage) that required intervention during RVAD + LVAD support. On the contrary, thrombotic events never occurred during biventricular support in our experience.…”
Section: Discussionmentioning
confidence: 96%